Understanding the solution-diffusion mechanism in gas separation membrane for engineering students - Ismail, Ahmad Fauzi; Kusworo, Tutuk Djoko; Mustafa, Azeman; Hasbullah, Hasrinah (2005)

(untitled)
An ongoing struggle for many lecturers is to motivate their students to learn and understand what they learn. Students seem to be particularly unmotivated to learn materials that appear uninteresting to them or unrelated to their own life experiences and career goals. However, educational developments are an important process for the students to adapt to the new and interesting phenomenon. So that, they can fully appreciate the technical breakthrough in certain field that leads to the commercialization of certain research products. Membrane technology is one of the successful products or processes that has been commercialized for gas mixture separation. This process employs the established solution-diffusion model in order to explain the transport of gases in polymeric membrane. In this paper, we derive simple phenomenological equations for transport of gases in membrane based on the solution-diffusion model.